2004
DOI: 10.1158/1078-0432.ccr-04-0379
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Vascular Endothelial Growth Factor-C and -D Expression in Human Pancreatic Cancer

Abstract: Purpose: The aim of this study was to evaluate the expression of vascular endothelial growth factor (VEGF)-C and -D in pancreatic cancer and to reveal its relation to lymph node metastasis.Experimental Design: Formalin-fixed, paraffin-embedded blocks were obtained from 58 patients with pancreatic head cancer. All of the patients underwent a curative resection. The total number of resected lymph nodes was 1,058. The expressions of VEGF-C and -D were evaluated by immunohistochemical staining. To evaluate the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(78 citation statements)
references
References 29 publications
(30 reference statements)
3
74
0
1
Order By: Relevance
“…It is noteworthy that lymph node metastasis and lymphatic invasion are correlated with CD133 expression, as a recent study demonstrated that a melanoma cell line highly enriched with CD133-expressing cells concomitantly expresses lymphoangiogenic markers, vascular endothelial growth factor receptor (VEGFR)-3 and lymphatic vessel endothelial hyaluronan receptor (LYVE)-1 (Monzani et al, 2007). As possible correlation between VEGF-C expression and lymphangiogenesis has previously been described (Kurahara et al, 2004;Mohammed et al, 2007), we examined VEGF-C expression in pancreatic cancer specimens and found it to be significantly associated with CD133 expression (Table 2). This suggests that CD133-positive pancreatic carcinoma cells promote lymphatic metastasis not only by inducing lymphangiogenesis, but also by facilitating self-entry into the lymphatic system.…”
Section: Discussionmentioning
confidence: 91%
“…It is noteworthy that lymph node metastasis and lymphatic invasion are correlated with CD133 expression, as a recent study demonstrated that a melanoma cell line highly enriched with CD133-expressing cells concomitantly expresses lymphoangiogenic markers, vascular endothelial growth factor receptor (VEGFR)-3 and lymphatic vessel endothelial hyaluronan receptor (LYVE)-1 (Monzani et al, 2007). As possible correlation between VEGF-C expression and lymphangiogenesis has previously been described (Kurahara et al, 2004;Mohammed et al, 2007), we examined VEGF-C expression in pancreatic cancer specimens and found it to be significantly associated with CD133 expression (Table 2). This suggests that CD133-positive pancreatic carcinoma cells promote lymphatic metastasis not only by inducing lymphangiogenesis, but also by facilitating self-entry into the lymphatic system.…”
Section: Discussionmentioning
confidence: 91%
“…23,24 However, Clarijs et al, 25 reported newly formed lymph vessels within the solid tumors using double staining with CD31 and PAL-E. Others have recently observed intratumoral lymphatics in melanomas, 26,27 breast, 28 head and neck, 29,30 pancreatic carcinoma, 31 and islet cell tumor. 32 A recent study detected intratumoral lymphatics in 91% of colorectal carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with the institutional guidelines of our hospital, tissue specimens were collected after delivery of informed consent (Kurahara et al, 2004).…”
Section: Methodsmentioning
confidence: 99%